Trends of Nepal’s Import Duties: Implications with Future Trade Liberalization - Research Department, Special Studies Division (NRB Economic Review, 2004)
Nepal is accelerating the process of trade liberalization that had commenced in the mid-eighties; this is reflected in membership of WTO, agreement of a framework for a free trade area (FTA) in south Asia and entering an FTA with BIMST-EC. Since import duties are presently an important source of government revenue, the likely impact of trade liberalization on this important revenue source has to be evaluated. The study addresses this felt need through an elasticity and buoyancy analysis of import duties over the span of fiscal year 1980/81 to 2001/2002 as well as analyzing the responsiveness of Nepal’s import duties through empirical regression and five year ahead projection. The paper finds low measure of elasticity and buoyancy as well as low elasticity of import duties, although five-year projections do not suggest a decline in contribution to government revenue. The prior indicate low productivity and responsiveness of the domestic tax base suggesting a need to accelerate reforms of the tax administrative system while the latter indicates that diversification of the import basket would be appropriate.